Implementation of E-Business and Organizational Support Towards Green Human Resource Management - Nur, Hafni Rizanuddin; Narimawati, Umi; Syafei, M Yani (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to analyse the application of e-business and organisational support to work ethics in realising Green Human Resource Management (GHRM). GHRM is a program that helps create a friendly workforce that respects the culture in an organisation, and one of the factors is that work ethics influences it. The research method used is quantitative, with the analytical technique being structural equation modelling analysis via SmartPLS 3.0. The research sample was 282 academic community members at universities in the Cirebon, Indramayu, Majalengka and Kuningan areas, with the sampling technique carried out using cluster proportional random sampling. The reseach of this study found that organizational support in this study had the lowest influence in moving towards GHRM. This research provides recommendations for improving the internal organization, especially in improving the culture of collaboration, coordination and cooperation, is vital in improving Green Human Resource Management.